Bangladesh - Policies for Mainstreaming Strategic Environmental Assessment in the Urban Development of Greater Dhaka - World Bank (Washington, DC, 2013)
This policy note focuses on analyzing critical institutional and planning issues affecting Dhaka's Metropolitan Area, and suggests policy recommendations for introducing sound urban environmental planning to improve the quality of life by mitigating and reversing environmental degradation. The report concludes with urgent recommended actions to address gaps in urban planning and environmental management that focus on developing the Dhaka Metropolitan Development Plan Land Use Map, by demarcating and publishing notification of ecologically and environmentally sensitive areas; resolving conflict arising from multiple functions of Rajdhani Unnayan Katripakkha; strengthening the detailed area plan planning process, engaging stakeholders in urban planning, and bringing other actors on board.